One year experience using mycobacterial blood cultures to diagnose tuberculosis in patients with prolonged fever in Vietnam - Diep NT Nguyen; Trung V Nguyen; Trinh T Dao; Lam T Nguyen; Peter Horby; Kinh Van Nguyen; Heiman FL Wertheim (Journal of Infection in Developing Countries)
Introduction: To evaluate the use of mycobacterial blood cultures (MBC) in diagnosing tuberculosis (TB) in patients with prolonged fever admitted to a Vietnamese referral hospital. Results: MBCs from 94 patients (66% male; median age 33 years; 75% HIV positive) were evaluated: 14 were mycobacterium positive (all HIV positive), and MBC was the only positive specimen in 9 cases (41%). Three positive cases were identified as Mycobacterium avium and the remaining M. tuberculosis (one case could not be identified). Conclusion: MBC can be a valuable additional method to diagnose TB, particularly in immunosuppressed HIV patients when sputum cannot be collected.